1990
DOI: 10.1161/01.hyp.15.5.528
|View full text |Cite
|
Sign up to set email alerts
|

Subclasses of cyclic GMP-specific phosphodiesterase and their role in regulating the effects of atrial natriuretic factor.

Abstract: Two subclasses of cyclic guanosine monophosphate (GMP) -specific phosphodiesterases were identified in vascular tissue from several beds. The activity of one subclass (phosphodiesterase IB) was stimulated severalfold by calmodulin and selectively inhibited by the phosphodiesterase inhibitor TCV-3B. The activity of the other subclass (phosphodiesterase IC) was not stimulated by calmodulin and was selectively inhibited by the phosphodiesterase inhibitor M&B 22,948. To assess the involvement of both subclasses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Interpretation of the results presented up to this point depends in part on previous descriptions of the effects of ANF (Cramb et al, 1987;Anand-Srivastava et al, 1989;Rugg et al, 1989;McCall and Fried, 1990), LY83583 (Schmidt et al, 1985;MacLeod and Diamond, 1986), and M&B22948 (Lugnier et al, 1983;Brunkhorst et al, 1989;Weishaar et al, 1990) on cGMP levels in heart. Therefore, 125I-cGMP radioimmunoassay was used to confirm that the key elements of previous findings were applicable to isolated ventricular myocytes under the present experimental conditions.…”
Section: Effects Of Anf Ly83583 and Mandb22948 On Cgmp Levels In Myocmentioning
confidence: 80%
See 1 more Smart Citation
“…Interpretation of the results presented up to this point depends in part on previous descriptions of the effects of ANF (Cramb et al, 1987;Anand-Srivastava et al, 1989;Rugg et al, 1989;McCall and Fried, 1990), LY83583 (Schmidt et al, 1985;MacLeod and Diamond, 1986), and M&B22948 (Lugnier et al, 1983;Brunkhorst et al, 1989;Weishaar et al, 1990) on cGMP levels in heart. Therefore, 125I-cGMP radioimmunoassay was used to confirm that the key elements of previous findings were applicable to isolated ventricular myocytes under the present experimental conditions.…”
Section: Effects Of Anf Ly83583 and Mandb22948 On Cgmp Levels In Myocmentioning
confidence: 80%
“…Correspondingly, after M&B22948 treatment, a threshold dose of ANF gave rise to a maximally effective increase in cGMP. M&B22948 also potentiates ANF's vasodilatory and natriuretic effects in rats and rabbits (Weishaar et al, 1990) and its stimulation of Na+/K+/2CI-cotransport in vascular smooth muscle (O'Donnell and Owen, 1986). Fifth, pretreatment with a maximally effective dose of 8-Br-cGMP eliminated the ability of ANF to decrease cell volume.…”
Section: Is Cgmp the Second Messenger For Anf-induced Myocyte Shrinkage?mentioning
confidence: 91%
“…This compound selectively abolished the endothelium-dependent relaxation induced by zaprinast in rat aortic rings, and in the presence of L-arginine, this inhibition by L-NMMA was completely restored ( Figure 6). Recently, Weishaar et al (1990) showed that zaprinast significantly potentiated the in vitro vascular relaxant response to atrial natriuretic factor (ANF). Altogether these observations suggest that the relaxant effects of zaprinast are due to the inhibition of the hydrolysis of cyclic GMP formed in response to EDRF released from endothelial cells (this study) or following stimulation of particulate guanylate cyclase by ANF (Weishaar et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Weishaar et al (1990) showed that zaprinast significantly potentiated the in vitro vascular relaxant response to atrial natriuretic factor (ANF). Altogether these observations suggest that the relaxant effects of zaprinast are due to the inhibition of the hydrolysis of cyclic GMP formed in response to EDRF released from endothelial cells (this study) or following stimulation of particulate guanylate cyclase by ANF (Weishaar et al, 1990). It is well established that in cardiac tissue from different species, PDE IV inhibitors do not cause an inotropic effect by themselves (Gristwood et al, 1986a,b;England, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The c-GMP is degraded to guanosine monophosphate which does not have the above effects of c-GMP. This process is enhanced by type 5 phosphodiesterase (PDE 5) [3] . Sildenafil is a new drug which inhibits PDE 5 and therefore is able to keep cellular c-GMP levels high.…”
Section: Introductionmentioning
confidence: 99%